THE BLACK ARIEL: CULTURAL CRITICISM AND THE EVOLUTION OF REPRESENTATION IN DISNEY'S THE LITTLE MERMAID (2024) LIVE-ACTION ADAPTATION - Michael Alberth Latupeirissa; Erfani Wahida; Varelina Aulia Firmansyah; Nisrina Khansa Adhira; Shalma Ramadhani Kusuma; Irma Adini R.; Noora Haidar Bawazier; Rina Saraswati, M.Hum.; Pujo Sakti Nur Cahyo, M.Hum. (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This mini-article explores the live-action adaptation of Disney’s The Little Mermaid (2023) through cultural criticism, focusing on Ariel's portrayal. It highlights her significance as a black-skinned character portrayed by actress Halle Bailey within a historically white narrative and argues that this adaptation critiques dominant cultural narratives that marginalize Black experiences. By reimagining Ariel, the film empowers Black representation in mainstream media and encourages audiences to engage with the complexities of identity and freedom, ultimately challenging perceptions of race in storytelling.